Personalised education as a school community of friendship - Pérez Guerrero, Javier (Journal of Philosophy of Education, 2021)
Many teachers believe that becoming friends with their pupils compromises their status as teachers because they regard friendship as a role that is incompatible with that status. However, to consider friendship as a typical relationship or social interaction does not reflect the classical idea of friendship. In a classical approach to friendship, a distinction is made between friendship as an intimate concordant duality and its manifestation or operative exercise, which is by necessity social and is regulated by what is right and fair in the exchange of goods typical of every community. Therefore, a school community may become a community of friendship to the extent that its educational purposes are fostered and strengthened by friendship, and what is right and fair in relationships and exchange of goods is respected. Personalised education can flourish in a school community of friendship because the reciprocity inherent to friendship emphasises the personal character of pupils and teachers, and promotes the capacity for coexistence of the students, which is a pre-eminent aim of personalised education.
Keywords: community of friends; educational relationship; fairness; personalised education; social type; WOS(2); Scopus